Suboptimal drug exposure leads to selection of different subpopulations of ceftazidime-avibactam-resistant Klebsiella pneumoniae carbapenemase-producing Klebsiella pneumoniae in a critically ill patient. (December 2021) - Gaibani, Paolo; Gatti, Milo; Rinaldi, Matteo; Crovara Pesce, Cristina; Lazzarotto, Tiziana; Giannella, Maddalena; Lombardo, Donatella; Amadesi, Stefano; Viale, Pierluigi; Pea, Federico; Ambretti, Simone
Highlights: Klebsiella pneumoniae carbapenemase-producing Klebsiella pneumoniae (KPC-Kp) Suboptimal ceftazidime-avibactam exposure is associated to resistance in KPC-Kp Mutations within bla KPC-3 are associated to resistance to ceftazidime-avibactam Mixed subpopulations harboring different bla KPC genes associated to hybrid phenotype Abstract: Objectives: Ceftazidime-avibactam (CAZ-AVI) is a promising novel agent with activity against carbapenem-resistant Enterobacteriaceae . Here, we describe the dynamic evolution of a Klebsiella pneumoniae carbapenemase-producing Klebsiella pneumoniae (KPC-Kp) infection in a critically ill patient treated with CAZ-AVI-tigecycline combination therapy. Methods: Whole-genome sequencing was performed on longitudinal intrapatient KPC-Kp strains isolated from different sites during CAZ-AVI treatment. The pharmacokinetic/pharmacodynamic (PK/PD) analysis was performed on the basis of therapeutic drug monitoring of ceftazidime. Results: The development of resistance due to mutations in the blaKPC gene was observed in KPC-Kp strains isolated from bronchoalveolar lavage and blood during CAZ-AVI treatment. PK/PD analysis demonstrated that during the first days of treatment CAZ- AVI blood exposure was suboptimal (steady-state concentration/minimum inhibitory concentration ratio 2.85). Of note, the low antibiotic pressure may have selected hybrid subpopulations harboring bla KPC-3 and T243M mutation in KPC-Kp isolated from bronchoalveolar lavage and D179Y mutation in those isolated from blood. Conclusion: These results suggest the high adaptability of KPC to CAZ-AVI due to the rapid evolution of resistance and highlight the importance of identifying the optimal PK/PD target to prevent such an event from occurring again in a critically ill patient with pneumonia due to KPC-Kp.